(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study was conducted to demonstrate the Assessing of Effectiveness of electronic technology on record management in Barangay Project 6 Quezon City; the research determined to provide knowledge to the readers about the importance and efficiency of using electronic technology and also to identify how the impact of electronic technologies help the employee in record management. At the present time, technology has a great impact on our daily lives, not only in the office field but these technologies are also used when it comes to business, organization, and communications. The researchers used qualitative instruments to examine the assessing the effectiveness of electronic technology on record management for every employee of Barangay Project 6 Quezon City, and the proponents used the survey questionnaire and face-to-face interviews as well as conducted almost an hour of discussion and gave the opportunity to the respondents to share more experience in using electronic technology. The respondents of this study are those who belong to Barangay Project 6 Staff, who are limited to four respondents (4). The type of questionnaire used for interview questions will be in the form of Open-ended questions, which are answerable verbally. Upon proceeding to results and discussion, the researcher found out the respondent’s age profile is 21 to 30 years old and 51 above with the same count. The majority of the profile of respondents according to educational attainment are college graduates and the majority profile of the respondents according to Position is Admin Staff of Barangay.